Promotion as part of the marketing mix and its application in enterprise activities - Michał Roman; Łukasz Zgiep (Polityki Europejskie, Finanse i Marketing)
Article presents the concept of marketing-mix in manufacturing companies. Under this idea, it is possible to specify at least four basic components: product, promotion, distribution and price. Each element could be taken into account to a greater or lesser degree in business operations, but it is always the essence of marketing. It is understood that in order to achieve a particular purpose companies have to use various combinations of tools and marketing activities to achieve maximum profit or sales. This article attempts to characteristics of the two companies marketing food products (case study). The study focuses attention on promotional activities and its importance in the field of marketing, for example, two companies Agros Nova and Frito-Lay.